2017
DOI: 10.1093/scan/nsx006
|View full text |Cite
|
Sign up to set email alerts
|

Violent offenders respond to provocations with high amygdala and striatal reactivity

Abstract: The ability to successfully suppress impulses and angry affect is fundamental to control aggressive reactions following provocations. The aim of this study was to examine neural responses to provocations and aggression using a laboratory model of reactive aggression. We used a novel functional magnetic resonance imaging point-subtraction aggression paradigm in 44 men, of whom 18 were incarcerated violent offenders and 26 were control non-offenders. We measured brain activation following provocations (monetary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 43 publications
1
45
1
Order By: Relevance
“…These indicate that when facing angry expressions, the later stage of actual inhibitory control of the motor control system is disrupted in reactively aggressive adolescents. The present results are a useful supplement to our previous studies and are consistent with existing studies using fMRI technology (Beyer et al, 2015;da Cunha-Bang et al, 2017;Jiang et al, 2018). According to the ICM, when presented angry expressions, reactively aggressive adolescents engage in more hostile interpretations, thereby impairing the later stage of response inhibition (Wilkowski and Robinson, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These indicate that when facing angry expressions, the later stage of actual inhibitory control of the motor control system is disrupted in reactively aggressive adolescents. The present results are a useful supplement to our previous studies and are consistent with existing studies using fMRI technology (Beyer et al, 2015;da Cunha-Bang et al, 2017;Jiang et al, 2018). According to the ICM, when presented angry expressions, reactively aggressive adolescents engage in more hostile interpretations, thereby impairing the later stage of response inhibition (Wilkowski and Robinson, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Behavioral studies have shown that when presented with angry expressions, response inhibition is impaired in reactively aggressive adolescents (Denson et al, 2011). Brain imaging studies have found that when individuals are presented with angry expressions, orbitomedial prefrontal cortex (OMPFC) reactivity and functional connectivity from limbic system (such as in the caudate nucleus and amygdala) to the OMPFC are significantly and negatively correlated with reactive aggression (Beyer et al, 2015;da Cunha-Bang et al, 2017;Jiang et al, 2018). The OMPFC is associated with response inhibition in hostile situations (Koenigs and Tranel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, these findings may support the theory of disturbed fronto-limbic functioning as a possible causal factor for child sexual offending regardless of pedophilia. Interestingly, a reduced fronto-limbic functional connectivity (as a response to provocations) has also been shown for violent and psychopathic offenders (69,70). From studies with healthy subjects, it is known that there is a strong top-down inhibitory control of prefrontal over limbic structures (especially amygdala), mediating responses to provocations [for review see: (71)].…”
Section: Functional Imaging-functional Magnetic Resonance Imagingmentioning
confidence: 99%
“…The PSAP has proved useful for probing behavioral responses related to reactive aggression (Cherek, Tcheremissine, & Lane, ). It has been demonstrated that criminally‐violent individuals (Cherek, Moeller, Schnapp, & Dougherty, ; Cherek, Lane, Dougherty, Moeller, & White, ; da Cunha‐Bang et al, ) and patients diagnosed with borderline personality and intermitted explosive disorder (New et al, ) respond more aggressively during the PSAP than healthy, non‐violent individuals. Thus, the PSAP represents a potentially useful probe for aggression‐related brain function.…”
Section: Introductionmentioning
confidence: 99%